Neuropsychological assessment as an objective tool to monitor treatment response in anti-N-methyl-D-aspartate receptor encephalitis. (8th June 2018) - Sieg, Erica; Brook, Michael; Linnoila, Jenny; VanHaerents, Stephen
Abstract : We report a 1-year follow-up of a young woman with anti-N-methyl-D-aspartate receptor encephalitis. Management of autoimmune encephalitis remains challenging as objective and clinically relevant biomarkers are sought, which allow for the monitoring of treatment response. While further investigation is required, we believe that this case highlights the importance of following a comprehensive neuropsychological profile as a clinically relevant biomarker to guide therapeutic decision-making. By relying on the neuropsychological assessment of the patient, treatment with more toxic medications was avoided and her antiepileptic drug regimen was simplified.